To a widow with children - García, Lionel G. (Arte Publico Press, 1994)
A love story set in the Southwest during the last century. The heroine is Maria, a poor, beautiful young widow with four naughty children whom the local sheriff wants to send to an orphanage. The situation is saved by the arrival of Benjamin, a handsome pistolero from Mexico.
Keywords: City and town life -- Fiction; Humorous fiction.; Man-woman relationships -- Fiction; Widows -- Fiction; Texas -- Fiction; Humorous fiction